Systemic methodology for risks evaluation and management in the energy and mining sectors (SYSMEREM-EMS) using bayesian networks. (15th May 2018) - Rodriguez-Ulloa, Ricardo
Abstract: The paper's purpose was to show a systemic methodology for risks evaluation and management in the energy and mining sectors (SYSMEREM-EM) and its application in the Peruvian context. For this purpose, this paper shows the combination of systemic approaches and artificial intelligence technology. Thus, for the processes' modelling of the value chains in both sectors, Soft Systems Methodology (SSM) was used; for the elucidation of the risks causalities embedded in dangerous events existing in the processes, System Dynamics' causal diagrams were used; and for risks' evaluation and management, the application of Bayesian networks' expert systems for decision-making was the approach used. These three techniques were used, in this sequence, within an overall framework. The paper ends with some comments about lessons learned and recommendations for further research.